Lithium battery positive electrode material, preparation method and application thereof
Patent Information
- Application Number
- CN202510735176.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2045-06-04
AI Technical Summary
[0005]本发明的目的在于针对现有方法制备得到的O2相正极材料存在克容量和倍率性能较差的问题,而提供了一种锂电正极材料及其制备方法,通过设计锂电正极材料颗粒内部具有两端贯穿到颗粒表面的裂纹,并使得具有所述裂纹的颗粒数占正极材料总颗粒数的比例在40%以上,从而提高所得正极材料的克容量性能和倍率性能
[0030] Beneficial effects: The key to this invention lies in the design of the crack structure inside the cathode material particles, so that the number of particles with cracks extending from both ends to the particle surface accounts for more than 40% of the total number of cathode material particles. At this time, the internal through cracks help to increase the exposed surface inside the cathode material particles, provide more reactive active sites, and help to increase the direct contact between the cathode material and lithium ions in the electrolyte, thereby improving the diffusion rate of lithium ions during charging and discharging, and thus improving the capacity performance and rate performance of the cathode material.
Smart Images

Figure CN120581585B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a lithium battery cathode material, its preparation method, and its application. Background Technology
[0002] High-energy-density lithium-ion batteries have long played a crucial role in advancing consumer electronics, electric vehicles, and large-scale energy storage, leading to ever-increasing demands for their energy density. The energy density of lithium-ion batteries is primarily limited by the cathode material, with current main cathode materials including LiCoO2 (LCO) and LiNi. x Mn y Co (1-x-y) O2 (NMC), LiMn2O4 and LiFePO4, etc.
[0003] LCO cathode materials possess the highest compaction density and volumetric energy density, playing an irreplaceable role in consumer electronics and other compact devices. One effective way to improve the energy density of LCO cathode materials is to increase their charging voltage. However, when the charging voltage exceeds 4.55V, the traditional O3 phase LCO begins to undergo an irreversible phase transition (O3→H1-3), leading to a rapid decline in the capacity and cycle performance of the LCO material. Therefore, further improvements to the structure of LCO materials are needed to enhance their charge-discharge capacity, structural stability, and cycle performance.
[0004] O2-phase LCO is a thermodynamically metastable phase, possessing a more stable structure and better electrochemical performance than O3-phase LCO. However, in conventional LCO preparation methods, the high-temperature sintering of lithium and cobalt precursors typically produces the O3 phase, thus usually utilizing P2-type Na... x CoO2 after Li + / Na + Ion replacement is used to synthesize O2-phase LCO. Aqueous solution ion replacement is a common method for synthesizing O2-phase LCO cathode materials. However, existing methods suffer from long replacement cycles (≥6h) due to limitations in the preparation process, resulting in low production capacity and high material costs. Furthermore, the specific capacity and rate performance of the cathode materials prepared using this method have limited potential for improvement. Summary of the Invention
[0005] The purpose of this invention is to address the problem of poor specific capacity and rate performance of O2 phase cathode materials prepared by existing methods, and to provide a lithium battery cathode material and its preparation method. By designing the lithium battery cathode material particles to have cracks extending from both ends to the particle surface, and ensuring that the number of particles with the cracks accounts for more than 40% of the total number of cathode material particles, the specific capacity and rate performance of the obtained cathode material are improved.
[0006] In a first aspect, the present invention provides a lithium-ion battery cathode material, the lithium-ion battery cathode material comprising a plurality of particles, at least a portion of the particles having cracks extending from both ends to the particle surface, and the number of particles having the cracks accounting for more than 40% of the total number of particles in the lithium-ion battery cathode material; the general chemical formula of the lithium-ion battery cathode material is LiMa. 1-x Me x O2, wherein 0≦x≦0.05, Ma is selected from at least one of Co, Ni, and Mn, and Me is selected from at least one of Sc, Ti, V, Cr, Fe, Cu, and Zn.
[0007] In a preferred embodiment, the width of the crack is 20–300 nm.
[0008] In a preferred embodiment, the length of the crack is 3 to 20 μm.
[0009] In a preferred embodiment, Ma contains Co as well as Ni and / or Mn.
[0010] In a preferred embodiment, the molar ratio of Co to Ni and / or Mn is 1:(0.02 to 0.06).
[0011] In a preferred embodiment, Me is selected from at least one of V, Ti, and Zn.
[0012] In a preferred embodiment, the particle size of the lithium battery cathode material is 3–20 μm.
[0013] In a preferred embodiment, the compaction density of the lithium-ion battery cathode material is 4.15–4.25 g / cm³. 3 .
[0014] Secondly, the present invention provides a method for preparing a lithium-ion battery cathode material. The preparation method includes the following steps: S1. Mixing a lithium-ion battery cathode material precursor with a sodium source and then sintering the mixture to obtain an intermediate product; S2. Mixing a lithium source, a reducing agent, and the intermediate product obtained in step S1 to perform a hydrothermal displacement reaction. The reducing agent is selected from at least one of oxalate, citrate, sulfite, nitrite, and vitamin C. The molar ratio of lithium ions in the lithium source to sodium ions in the intermediate product is greater than 3:1. The intermediate product is added 10–30°C before the reaction system reaches the hydrothermal displacement reaction temperature. After the hydrothermal displacement reaction is completed, the mixture undergoes solid-liquid separation, washing, and drying to obtain the solid, which is the lithium-ion battery cathode material. The general chemical formula of the lithium-ion battery cathode material precursor is Ma. 1-x Me x O yWhere 0≦x≦0.05, x and y satisfy the law of charge conservation, Ma is selected from at least one of Co, Ni, and Mn, and Me is selected from at least one of Sc, Ti, V, Cr, Fe, Cu, and Zn.
[0015] In a preferred embodiment, in step S1, Me is selected from at least one of V, Ti, and Zn.
[0016] In a preferred embodiment, in step S1, the sodium source is selected from at least one of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium nitrate, sodium sulfate, sodium acetate, and sodium oxalate.
[0017] In a preferred embodiment, in step S1, the molar ratio of the metal ions of the lithium battery cathode material precursor to the sodium ions of the sodium source is 1:(0.75~1).
[0018] In a preferred embodiment, in step S1, the sintering conditions include: a sintering temperature of 700–950°C and a sintering time of 12–36 h.
[0019] In a preferred embodiment, in step S2, the lithium source is selected from at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium chloride, lithium bromide, and lithium iodide.
[0020] In a preferred embodiment, in step S2, the molar ratio of the Ma source ion of the intermediate product to the reducing agent is 1:(0.05~0.25).
[0021] In a preferred embodiment, in step S2, the conditions for the hydrothermal replacement reaction include: a reaction temperature of 100–180°C, a reaction time of 1–6 h, a stirring frequency of 20–50 Hz, and a reaction pressure of 0–2.0 MPa.
[0022] In a preferred embodiment, in step S2, the solid content of the reaction system during the hydrothermal replacement reaction is 40-60 wt%.
[0023] In a preferred embodiment, step S2, the hydrothermal replacement reaction process includes: first mixing a lithium source, a reducing agent, and water to obtain a premix; then heating the premix to 80-150°C and adding an intermediate product; and then continuing to heat the mixture to 100-180°C to carry out the reaction.
[0024] In a preferred embodiment, in step S2, the concentration of lithium ions in the premix is 15–40 mol / L.
[0025] In a preferred embodiment, in step S2, the heating rates of the premix and the mixture are each independently 1.0 to 1.5 °C / min.
[0026] In a preferred embodiment, in step S2, the mass ratio of water to solid added during the washing process is (1-3):1.
[0027] In a preferred embodiment, in step S2, the water washing is stopped when the concentration of metal ions in the water washing solution is less than 200 ppm.
[0028] Thirdly, the present invention also provides a lithium-ion battery cathode material prepared by the above method.
[0029] Fourthly, the present invention also provides the application of the above-mentioned lithium battery cathode material in lithium-ion batteries.
[0030] Beneficial effects: The key to this invention lies in the design of the crack structure inside the cathode material particles, so that the number of particles with cracks extending from both ends to the particle surface accounts for more than 40% of the total number of cathode material particles. At this time, the internal through cracks help to increase the exposed surface inside the cathode material particles, provide more reactive active sites, and help to increase the direct contact between the cathode material and lithium ions in the electrolyte, thereby improving the diffusion rate of lithium ions during charging and discharging, and thus improving the capacity performance and rate performance of the cathode material.
[0031] In this invention, a specific reducing agent is introduced during the hydrothermal replacement process, and the timing of the intermediate product's addition to the reaction system is controlled. Specifically, the intermediate product is added 10–30°C before the reaction system reaches the hydrothermal replacement reaction temperature. Simultaneously, the external lithium concentration is controlled during the hydrothermal replacement reaction. Since the reaction system already has a sufficiently high temperature when the precursor oxide is added, the ion diffusion rate is fast. In addition, the high lithium ion concentration difference between the external lithium solution and the interior of the precursor oxide particles greatly improves the ion exchange rate between sodium ions inside the precursor oxide and lithium ions in the solution at the moment of contact. This facilitates the optimization of the cracking design of the through-cracks inside the cathode material particles through the synergistic control of the above steps. While increasing the proportion of particles with the aforementioned cracks in the total number of cathode material particles, it does not significantly affect the surface morphology and compaction density of the cathode material, thereby achieving the goal of improving the capacity and rate performance of the cathode material.
[0032] In a preferred embodiment, when Ma contains Co, Ni, and Mn simultaneously, due to the synergistic effect of Ni-Co-Mn elements, the Co structure provides excellent ionic conductivity under high-voltage charge and discharge, Ni ensures a large reversible capacity, and Mn does not participate in electrochemical reactions during charge and discharge, playing a role in stabilizing the material structure. This can further improve the rate performance while ensuring that the lithium battery material has good capacity performance. Attached Figure Description
[0033] Figure 1 This is a cross-sectional SEM image of the lithium-ion battery cathode material prepared in Example 1.
[0034] Figure 2 This is a cross-sectional SEM image of the reference lithium-ion battery cathode material prepared in Comparative Example 1. Detailed Implementation
[0035] The lithium-ion battery cathode material provided by this invention comprises multiple particles, at least a portion of which have cracks extending from both ends to the particle surface. The number of particles with cracks accounts for more than 40% of the total number of particles in the lithium-ion battery cathode material, such as 40%, 50%, 60%, 70%, 80%, 90%, 100%, or any value between these values, more preferably more than 60%. In this invention, the method for testing the percentage of these particles can be: observing and calculating the number of particles with cracks using a scanning electron microscope (2K) image.
[0036] In this invention, the width of the crack is preferably 20–300 nm, such as 20 nm, 50 nm, 80 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, or any value between them. The length of the crack is preferably 3–20 μm, such as 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, or any value between them. This has the advantage of improving the capacity and rate performance of the cathode material because the internal through-cracks help increase the exposed surface area inside the cathode material particles, providing more reactive sites, and also help increase the direct contact between the cathode material and lithium ions in the electrolyte, thereby improving the diffusion rate of lithium ions during charging and discharging.
[0037] In this invention, the general chemical formula of the lithium-ion battery cathode material is LiMa. 1-x Me x O2, wherein 0 ≦ x ≦ 0.05, and x can be 0, 0.01, 0.02, 0.03, 0.04, 0.05 or any value between them; Ma is selected from at least one of Co, Ni, and Mn; Me is selected from at least one of Sc, Ti, V, Cr, Fe, Cu, and Zn, preferably from at least one of V, Ti, and Zn.
[0038] In this invention, Ma preferably contains Co and Ni and / or Mn. When Ma simultaneously contains Co and Ni, Co and Mn, or Co, Ni, and Mn, due to the synergistic effect among Ni, Co, and Mn elements, under high-voltage charge and discharge, the Co structure provides excellent ionic conductivity, Ni provides a large reversible capacity, and Mn does not participate in electrochemical reactions during charge and discharge, playing a role in stabilizing the material structure, which can further improve the rate performance of the lithium battery material. The molar ratio of Co to Ni and / or Mn is preferably 1:(0.02~0.06), such as 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, or any value between them.
[0039] In this invention, the particle size of the lithium-ion battery cathode material is preferably 3–20 μm, such as 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, or any value between them. In this invention, the particle size refers to the length of the longest axis of the particle, which can be measured using a laser particle size analyzer.
[0040] In this invention, the compaction density of the lithium-ion battery cathode material is preferably 4.15–4.25 g / cm³. 3 For example, 4.15 g / cm³ 3 4.18 g / cm 3 4.20g / cm 3 4.22g / cm 3 4.25g / cm 3 Or any value in between. In this invention, the method for measuring the compacted density can be: measurement using a powder compacted density tester.
[0041] The method for preparing the lithium-ion battery cathode material provided by this invention includes the following steps:
[0042] S1. The lithium battery cathode material precursor is mixed with a sodium source and then sintered to obtain an intermediate product;
[0043] S2. The lithium source, reducing agent and intermediate product obtained in step S1 are mixed and subjected to a hydrothermal replacement reaction. The reducing agent is selected from at least one of oxalate, citrate, sulfite, nitrite and vitamin C. The molar ratio of lithium ions in the lithium source to sodium ions in the intermediate product is greater than 3:1. The intermediate product is added 10 to 30°C before the reaction system is heated to the hydrothermal replacement reaction temperature. After the hydrothermal replacement reaction is completed, the solid is subjected to solid-liquid separation, water washing and drying. The resulting solid is the lithium battery cathode material.
[0044] In this invention, in step S1, the general chemical formula of the lithium-ion battery cathode material precursor is Ma. 1-x Me x Oy Wherein, 0≦x≦0.05, and x and y satisfy the charge conservation law. Ma is preferably at least one of Co, Ni, and Mn. Me is preferably at least one of Sc, Ti, V, Cr, Fe, Cu, and Zn, and more preferably at least one of V, Ti, and Zn. More preferably, Ma contains Co and Ni and / or Mn, that is, when Ma contains any one of the three cases of Co and Ni, Co and Mn, or Co, Ni, and Mn, it is more conducive to further improving the rate performance of the cathode material.
[0045] In this invention, in step S1, the one having Ma 1-x Me x O y The general-structured lithium-ion battery cathode material precursor can be commercially available or prepared using existing methods. Specifically, Ma 1-x Me x O y It can be obtained by heat treatment of Ma salt and optional Me salt, or by first co-precipitating Ma salt and optional Me salt with an alkaline precipitant, and then heat-treating the solid product after washing and drying.
[0046] In this invention, in step S1, the sodium source can be any existing compound that can provide sodium and can be used to prepare cathode materials, including but not limited to at least one of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium nitrate, sodium sulfate, sodium acetate, and sodium oxalate.
[0047] In this invention, in step S1, the molar ratio of the metal ions of the lithium battery cathode material precursor to the sodium ions of the sodium source is preferably 1:(0.75~1), such as 1:0.75, 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1 or any value between them.
[0048] In this invention, in step S1, the mixing method of the lithium-ion battery cathode material precursor and the sodium source can be any one of ball milling, grinding, or high-speed mixing, with high-speed mixing being preferred. The high-speed mixing preferably includes a primary mixing stage and a secondary mixing stage. This has the advantage of improving the mixing uniformity of the lithium-ion battery cathode material precursor and the sodium source because the sodium source has a large particle size and is prone to agglomeration; a two-stage high-speed mixing method can ensure mixing uniformity. Specifically, the rotation speed of the primary mixing stage is preferably 400–600 rpm, such as 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, or any value between them; the time is preferably 1–5 min, such as 1 min, 2 min, 3 min, 4 min, 5 min, or any value between them. The preferred rotational speed for the secondary mixing stage is 1000–1500 rpm, such as 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, or any value between them; the preferred time is 10–30 min, such as 10 min, 15 min, 20 min, 25 min, 30 min, or any value between them.
[0049] In this invention, the sintering conditions in step S1 preferably include: a sintering temperature of 700–950°C, such as 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, or any value between them; and a constant-temperature sintering time of 12–36 h, such as 12 h, 18 h, 20 h, 24 h, 28 h, 32 h, 36 h, or any value between them. The sintering process can be carried out in an air atmosphere or other oxygen-containing atmosphere.
[0050] In this invention, the lithium source can be any existing lithium-containing compound that can be used to prepare cathode materials, and specific examples include, but are not limited to, at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium chloride, lithium bromide, and lithium iodide.
[0051] In this invention, the reducing agent is selected from at least one of oxalate, citrate, sulfite, nitrite, and vitamin C. Specific examples include, but are not limited to, at least one of lithium oxalate, sodium oxalate, vitamin C, sodium citrate, lithium citrate, sodium sulfite, and sodium nitrite. Compared to other reducing agents (e.g., glucose), using the above-mentioned specific types of reducing agents can avoid the destruction of the cathode material's crystal structure during the hydrothermal replacement reaction, thus ensuring the integrity of the cathode material's crystal structure. Furthermore, in conjunction with controlling the amount of lithium ions added to the lithium source and the timing of the intermediate product addition during the hydrothermal replacement reaction, it achieves design control over the cracking of the cathode material particles, thereby contributing to the improvement of the battery's charge / discharge capacity and rate performance.
[0052] In this invention, in step S2, the molar ratio of lithium ions in the lithium source to sodium ions in the intermediate product is 3:1 or higher, more preferably (3-5):1, such as 3:1, 3.5:1, 4:1, 4.5:1, 5:1, or any value between them. When the molar ratio of lithium ions in the lithium source to sodium ions in the intermediate product is lower than the above range, there is a problem of low proportion of cathode material particles containing cross-sectional through cracks. This is because the low concentration of lithium ions in the solution leads to a decrease in the driving force for lithium-sodium ion exchange, which is not conducive to the formation of cross-sectional through cracks.
[0053] In this invention, in step S2, the molar ratio of Ma source ions to reducing agent in the intermediate product is preferably 1:(0.05-0.25), such as 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25 or any value between them.
[0054] In this invention, in step S2, the reaction temperature of the hydrothermal replacement reaction is preferably 100–180°C, such as 100°C, 120°C, 140°C, 150°C, 160°C, 180°C, or any value between them, more preferably 140–180°C. The reaction time of the hydrothermal replacement reaction is preferably 1–6 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, or any value between them. The hydrothermal replacement reaction is carried out under stirring, and the stirring frequency is preferably 20–50 Hz, such as 20 Hz, 30 Hz, 40 Hz, 50 Hz, or any value between them. This has the advantage of increasing the proportion of cathode material particles containing cross-sectional through-cracks, because appropriate stirring intensity can improve the mixing efficiency of precursor oxide with lithium ions in the hydrothermal system, increase the exchange rate of Li-Na ions, and thus further optimize the formation of through-cracks inside the cathode material particles. The preferred reaction pressure for the hydrothermal replacement reaction is 0–2.0 MPa, such as 0 MPa, 0.5 MPa, 1 MPa, 1.5 MPa, 2 MPa, or any value between them. This has the advantage of increasing the proportion of cathode material particles containing cross-sectional through cracks. This is because increasing the reaction pressure helps to increase the exchange rate of Li-Na ions in the hydrothermal replacement reaction, thereby further optimizing the formation of through cracks inside the cathode material particles.
[0055] In this invention, the solid content of the reaction system during the hydrothermal replacement reaction is preferably 40-60 wt%, such as 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, or any value between them. This is more conducive to increasing the effective contact between the precursor oxide and lithium ions, improving the exchange rate of Li-Na ions, and increasing the proportion of cathode material particles containing cross-sectional through cracks.
[0056] In this invention, in step S2, the hydrothermal displacement reaction is preferably carried out as follows: a lithium source, a reducing agent, and water are first mixed to obtain a premix; the premix is heated to 80–150°C, and an intermediate product is added; then the mixture is further heated to 100–180°C to carry out the reaction. The temperature at which the intermediate product is added to the reaction system is preferably 80–150°C, such as 80°C, 100°C, 120°C, 140°C, 150°C, or any value between them.
[0057] In this invention, the lithium ion concentration in the premix is preferably 15–35 mol / L, such as 15, 20, 25, 30, 35 mol / L or any value between them. This is more conducive to increasing the proportion of cathode material particles containing cross-sectional through cracks, because the greater the lithium ion concentration difference, the greater the driving force for Li-Na ion exchange, which is more conducive to the formation of cross-sectional through cracks inside the cathode material particles.
[0058] In this invention, the heating rate of the premix and the mixture is preferably independently 1.0 to 1.5 °C / min, such as 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 °C / min or any value between them. This has the advantage of increasing the proportion of cathode material particles containing cross-sectional through cracks, because an appropriate heating rate can increase the Li-Na ion exchange rate and promote the formation of cross-sectional through cracks inside the cathode material particles.
[0059] In this invention, the mass ratio of water to solid added during the washing process is (1-3):1, such as 1:1, 1.5:1, 2:1, 2.5:1, 3:1, or any value between them. During this washing process, hydrogen ions can rapidly exchange with residual sodium ions inside the solid particles, further optimizing the morphology of the interfacial broken particles, increasing the proportion of cathode material particles containing cross-sectional through cracks, while ensuring a good surface morphology of the cathode material.
[0060] In this invention, the water washing is stopped when the concentration of metal ions in the water washing solution is less than 200 ppm.
[0061] In this invention, the drying conditions preferably include: a temperature of 150℃ to 250℃, such as 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃ or any value between them; and a time of 5h to 20h, such as 5h, 8h, 10h, 12h, 15h, 18h, 20h or any value between them.
[0062] The present invention will be described in detail below through specific embodiments. These embodiments are intended to explain the invention and should not be construed as limiting it. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0063] Preparation Example 1: Precursor Material (Co) 0.97 Ni 0.01 Mn 0.02 Preparation of 3O4
[0064] Cobalt sulfate, nickel sulfate, and manganese sulfate were weighed according to a molar ratio of Co:Ni:Mn = 97:1:2, mixed thoroughly, and placed in a muffle furnace. The mixture was heated to 700℃ at a rate of 5℃ / min under air atmosphere and held for 3 hours. After natural cooling, the mixture was ground to obtain the precursor material (Co). 0.97 Ni 0.01 Mn 0.02 3O4 powder.
[0065] Preparation Example 2: Precursor Material (Co) 0.94 Ni 0.01 Mn 0.02 Ti 0.03 Preparation of 3O4
[0066] Cobalt sulfate, nickel sulfate, and manganese sulfate were weighed according to the molar ratio Co:Ni:Mn:Ti = 94:1:2:3, mixed evenly, and placed in a muffle furnace. The mixture was heated to 700℃ at a rate of 5℃ / min under air atmosphere and held for 3 hours. After natural cooling, the mixture was ground to obtain the precursor material (Co). 0.94 Ni 0.01 Mn 0.02 Ti 0.03 3O4 powder.
[0067] Example 1
[0068] This embodiment illustrates the preparation of a lithium-ion battery cathode material, and the specific process is as follows:
[0069] S1. Weigh out 0.720 kg (18.00 mol) of NaOH and 1.926 kg (8.00 mol) of Co3O4 powder according to a molar ratio of Na / Co = 0.75. Add them together to a high-speed mixer and mix at 500 rpm for 1 min, then at 1200 rpm for 20 min, ensuring no white spots remain on the surface of the material after mixing. Then, place the mixed material in a box furnace for high-temperature sintering in an air atmosphere. Increase the temperature to 900℃ at a rate of 5℃ / min and hold for 24 h. After holding, allow it to cool naturally to room temperature. After discharge, process the material using a jaw crusher, roller crusher, and sieve to obtain the semi-finished material Na. 0.75 CoO2.
[0070] S2. Weigh 0.307 kg of lithium hydroxide monohydrate (7.32 mol), 1.886 kg of lithium nitrate (27.35 mol), and 0.141 kg of lithium oxalate reducing agent (1.38 mol) and add them separately to 1 L of anhydrous salt water. Stir at 500 rpm until completely dissolved to obtain a premix, then transfer it to a hydrothermal reaction vessel. Set the stirring frequency to 45 Hz. Heat the premix to 140 °C at a heating rate of 1.3 °C / min. The pressure of the reaction system is 0.5 MPa. Weigh 1.000 kg of the semi-finished material Na prepared in step S1 above. 0.75 CoO2 was added to a sealed container and mixed with the premix. At this point, the solid content of the hydrothermal reaction system was 50% and the molar ratio of lithium ions to sodium ions was 5:1. The mixture was then heated to 160°C at a rate of 1.3°C / min and kept at this temperature for 4 hours. After the hydrothermal replacement was completed, the cathode material slurry was poured into a negative pressure filtration device for solid-liquid separation. During the water washing process, the mass ratio of water to solid was controlled at 2:1. After filtration and washing with salt water 8 times, the metal ion concentration of the washing liquid was <200ppm. After drying in a vacuum oven at 200°C for 10 hours, the lithium battery cathode material was finally obtained by sieving through a 300-mesh sieve.
[0071] like Figure 1 As shown, most of the lithium-ion battery cathode material particles prepared in Example 1 have cracks extending from both ends to the particle surface. Scanning electron microscopy (2K) observation and calculation showed that particles with these cracks accounted for 87.3% of the total number of particles in the lithium-ion battery cathode material. Furthermore, the particle size of this lithium-ion battery cathode material was 5–20 μm, the crack length was approximately 5–20 μm, and the crack width was approximately 50–300 nm.
[0072] Example 2
[0073] This embodiment illustrates the preparation of a lithium-ion battery cathode material, and the specific process is as follows:
[0074] S1. Weigh out 0.720 kg (18.00 mol) of NaOH and 1.700 kg (7.06 mol) of Co3O4 powder according to a molar ratio of Na / Co = 0.85. Add them together to a high-speed mixer and mix at 500 rpm for 1 min, then at 1200 rpm for 20 min, ensuring no white spots remain on the surface of the material after mixing. Then, place the mixed material in a box furnace for high-temperature sintering in an air atmosphere. Increase the temperature to 800℃ at a rate of 5℃ / min and hold for 24 h. After holding, allow it to cool naturally to room temperature. After discharge, process the material using a jaw crusher, roller crusher, and sieve to obtain the semi-finished material Na. 0.85 CoO2.
[0075] S2. Weigh 0.307 kg of lithium hydroxide monohydrate (7.32 mol), 1.131 kg of lithium bromide (13.02 mol), and 0.408 kg of sodium citrate reducing agent (1.58 mol) and add them separately to 1 L of anhydrous water. Stir at 500 rpm until completely dissolved to obtain a premix, then transfer it to a hydrothermal reaction vessel. Set the stirring frequency to 50 Hz. Heat the premix to 80 °C at a rate of 1.5 °C / min. The pressure of the reaction system is atmospheric pressure. Weigh 0.666 kg of the semi-finished material Na prepared in step S1 above. 0.85 CoO2 was added to a sealed container and mixed with the premix. At this point, the solid content of the hydrothermal reaction system was 40 wt% and the molar ratio of lithium ions to sodium ions was 4:1. The mixture was then heated to 100 ℃ at a rate of 1.0 ℃ / min and kept at this temperature for 6 hours. After the hydrothermal replacement was completed, the positive electrode material slurry was poured into a negative pressure filtration device for solid-liquid separation. During the water washing process, the mass ratio of water to solid was controlled at 3:1. After filtration and washing with salt water 8 times, the metal ion concentration of the washing liquid was <200 ppm. After drying in a vacuum oven at 200 ℃ for 10 hours, the lithium battery positive electrode material was finally obtained by sieving through a 300-mesh sieve.
[0076] In Example 2, at least some of the lithium-ion battery cathode material particles had cracks extending from both ends to the particle surface. Scanning electron microscopy (2K) observation and calculation showed that particles with these cracks accounted for 82.5% of the total number of particles in the lithium-ion battery cathode material. Furthermore, the particle size of this lithium-ion battery cathode material was 4–12 μm, the length of the cracks was approximately 4–12 μm, and the width was approximately 40–250 nm.
[0077] Example 3
[0078] This embodiment illustrates the preparation of a lithium-ion battery cathode material, and the specific process is as follows:
[0079] S1. Weigh out 0.720 kg (18.00 mol) of NaOH and 1.445 kg (6.00 mol) of Co3O4 powder according to the molar ratio Na / Co = 1, and add them together into a high-speed mixer. Mix at 500 rpm for 1 min, then at 1200 rpm for 20 min, until the surface of the material is free of white spots after mixing. Then, place the mixed material in a box furnace for high-temperature sintering in an air atmosphere. Increase the temperature to 700℃ at a rate of 5℃ / min and hold for sintering for 36 h. After holding, allow it to cool naturally to room temperature. After discharge, crush, roll crush, and sieve to obtain the semi-finished material NaCoO2.
[0080] S2. Weigh 0.307 kg of lithium hydroxide monohydrate (7.32 mol), 1.491 kg of lithium chloride (35.18 mol), and 0.136 kg of sodium nitrite reducing agent (1.97 mol) and add them separately to 1 L of anhydrous water. Stir at 500 rpm until completely dissolved to obtain a premix, then add it to a hydrothermal reaction vessel. Set the stirring frequency to 20 Hz. Heat the premix to 150 °C at a heating rate of 1.0 °C / min. The pressure of the reaction system is 0.5 MPa. Weigh 1.500 kg of the semi-finished material NaCoO2 prepared in step S1 above and add it to a sealed container. The mixture is mixed with the premix, at which point the solid content of the hydrothermal reaction system is 60 wt% and the molar ratio of lithium ions to sodium ions is 3:1. The mixture is then heated to 180°C at a rate of 1.5°C / min and kept at that temperature for 2 hours. After the hydrothermal replacement is completed, the positive electrode material slurry is poured into a negative pressure filtration device for solid-liquid separation. During the water washing process, the mass ratio of water to solid is controlled at 1:1. After filtration and washing with salt water 8 times, the metal ion concentration of the washing water is <200 ppm. After drying in a vacuum oven at 200°C for 10 hours, the lithium battery positive electrode material is finally obtained by sieving through a 300-mesh sieve.
[0081] The lithium-ion battery cathode material particles prepared in Example 3 have cracks extending from both ends to the particle surface. Scanning electron microscopy (2K) observation and calculation showed that particles with these cracks accounted for 80.3% of the total number of lithium-ion battery cathode material particles. Furthermore, the particle size of this lithium-ion battery cathode material was 3–10 μm, the length of the cracks was approximately 3–10 μm, and the width was approximately 50–200 nm.
[0082] Example 4
[0083] The lithium-ion battery cathode material was prepared according to the method of Example 1, except that in step S1, 0.720 kg (18.00 mol) of NaOH and 1.910 kg (8 mol) of the (Co+Mn+Ni) prepared in Example 1 were weighed according to the molar ratio Na / (Co+Mn+Ni) = 0.75.0.97 Ni 0.01 Mn 0.02 The 3O4 precursor powder was added to a high-speed mixer for mixing, and all other conditions were the same as in Example 1, thereby preparing the lithium battery cathode material.
[0084] The lithium-ion battery cathode material particles prepared in Example 4 have cracks extending from both ends to the particle surface. Observation and calculation using a scanning electron microscope (2K) showed that particles with these cracks accounted for 78% of the total number of lithium-ion battery cathode material particles. Furthermore, the particle size of this lithium-ion battery cathode material was 5–20 μm, the length of the cracks was approximately 5–20 μm, and the width was approximately 50–300 nm.
[0085] Example 5
[0086] The lithium-ion battery cathode material was prepared according to the method of Example 1, except that in step S1, 0.720 kg (18.00 mol) of NaOH and 1.910 kg (8.00 mol) of the (Co+Mn+Ni+Ti) preparation material of Example 2 were weighed according to the molar ratio Na / (Co+Mn+Ni+Ti) = 0.75. 0.94 Ni 0.01 Mn 0.02 Ti 0.03 The 3O4 precursor powder was added to a high-speed mixer for mixing, and all other conditions were the same as in Example 1, thereby preparing the lithium battery cathode material.
[0087] The lithium-ion battery cathode material particles prepared in Example 5 have cracks extending from both ends to the particle surface. Observation and calculation using a scanning electron microscope (2K) showed that particles with these cracks accounted for 75% of the total number of lithium-ion battery cathode material particles. Furthermore, the particle size of this lithium-ion battery cathode material was 5–20 μm, the length of the cracks was approximately 5–20 μm, and the width was approximately 50–300 nm.
[0088] Example 6
[0089] The lithium-ion battery cathode material was prepared according to the method of Example 1, except that in step S2, the amount of lithium oxalate reducing agent was 0.071 kg (0.7 mol), and the other conditions were the same as in Example 1. The lithium-ion battery cathode material was thus prepared.
[0090] The lithium-ion battery cathode material particles prepared in Example 6 have cracks extending from both ends to the particle surface. Scanning electron microscopy (2K) observation and calculation showed that particles with these cracks accounted for 71.5% of the total number of lithium-ion battery cathode material particles. Furthermore, the particle size of this lithium-ion battery cathode material was 5–20 μm, the length of the cracks was approximately 5–20 μm, and the width was approximately 30–200 nm.
[0091] Example 7
[0092] The lithium-ion battery cathode material was prepared according to the method of Example 1, except that in step S2, the heating rate of the premix and the mixture was 3°C / min, and the other conditions were the same as in Example 1, thereby obtaining the lithium-ion battery cathode material.
[0093] The lithium-ion battery cathode material particles prepared in Example 7 have cracks extending from both ends to the particle surface. Observation and calculation using a scanning electron microscope (2K) showed that particles with these cracks accounted for 74.1% of the total number of lithium-ion battery cathode material particles. Furthermore, the particle size of this lithium-ion battery cathode material was 5–20 μm, the length of the cracks was approximately 5–20 μm, and the width was approximately 50–200 nm.
[0094] Example 8
[0095] The lithium-ion battery cathode material was prepared according to the method of Example 1, except that in step S2, the heating rate of the premix and the mixture was 0.5℃ / min, and the other conditions were the same as in Example 1, thereby obtaining the lithium-ion battery cathode material.
[0096] The lithium-ion battery cathode material particles prepared in Example 8 have cracks extending from both ends to the particle surface. Scanning electron microscopy (2K) observation and calculation showed that particles with these cracks accounted for 72.6% of the total number of lithium-ion battery cathode material particles. Furthermore, the particle size of this lithium-ion battery cathode material was 5–20 μm, the length of the cracks was approximately 5–20 μm, and the width was approximately 50–150 nm.
[0097] Example 9
[0098] The lithium-ion battery cathode material was prepared according to the method of Example 1, except that in step S1, NaOH and Co3O4 powder were mixed using a ball mill at a speed of 1200 rpm for 20 min. All other conditions were the same as in Example 1, and the lithium-ion battery cathode material was thus prepared.
[0099] The lithium-ion battery cathode material particles prepared in Example 9 have cracks extending from both ends to the particle surface. Scanning electron microscopy (2K) observation and calculation showed that particles with these cracks accounted for 60.8% of the total number of lithium-ion battery cathode material particles. Furthermore, the particle size of this lithium-ion battery cathode material was 5–20 μm, the length of the cracks was approximately 5–20 μm, and the width was approximately 30–150 nm.
[0100] Comparative Example 1
[0101] The lithium-ion battery cathode material was prepared according to the method in Example 1, except that in step S2, the semi-finished material Na was added when the premix was heated to 60°C.0.75 CoO2, with all other conditions the same as in Example 1, thus preparing a reference lithium-ion battery cathode material.
[0102] like Figure 1 As shown, a small number of lithium battery cathode material particles prepared in Comparative Example 1 have cracks extending from both ends to the particle surface. According to the scanning electron microscope (2K) images and calculations, the number of particles with such cracks accounts for 28.3% of the total number of lithium battery cathode material particles.
[0103] Comparative Example 2
[0104] The lithium-ion battery cathode material was prepared according to the method of Example 1, except that in step S2, lithium oxalate reducing agent was not added when preparing the premix, and the other conditions were the same as in Example 1, thereby obtaining the reference lithium-ion battery cathode material.
[0105] In Comparative Example 2, a small number of lithium-ion battery cathode material particles had cracks extending from both ends to the particle surface. According to scanning electron microscopy (2K) images and calculations, the number of particles with such cracks accounted for 31.9% of the total number of lithium-ion battery cathode material particles.
[0106] Comparative Example 3
[0107] The reference lithium-ion battery cathode material was prepared according to the method of Example 1, except that in step S2, the amount of lithium nitrate was 0.212 kg (3.07 mol), and the molar ratio of lithium ions to sodium ions in the hydrothermal replacement reaction system was 1.5:1. All other conditions were the same as in Example 1, and the reference lithium-ion battery cathode material was thus prepared.
[0108] The reference lithium-ion battery cathode material particles prepared in Comparative Example 3 have cracks extending from both ends to the particle surface. Scanning electron microscopy analysis showed that particles with these cracks accounted for 33.5% of the total number of lithium-ion battery cathode material particles. Furthermore, the particle size of this reference lithium-ion battery cathode material was 5–20 μm, the length of the cracks was approximately 5–20 μm, and the width was approximately 30–150 nm.
[0109] Comparative Example 4
[0110] The reference lithium-ion battery cathode material was prepared according to the method of Example 1, except that in step S2, the same molar amount of glucose was used instead of lithium oxalate reducing agent, and the other conditions were the same as in Example 1, thereby obtaining the reference lithium-ion battery cathode material.
[0111] The reference lithium-ion battery cathode material particles prepared in Comparative Example 4 have cracks extending from both ends to the particle surface. Scanning electron microscopy analysis showed that particles with these cracks accounted for 36.4% of the total number of lithium-ion battery cathode material particles. Furthermore, the particle size of this lithium-ion battery cathode material was 5–20 μm, the crack length was approximately 5–20 μm, and the crack width was approximately 30–100 nm.
[0112] Test case
[0113] This test example is used to illustrate the relevant performance of the lithium battery cathode materials prepared in the above embodiments and comparative examples. The specific test methods are as follows and the results are shown in Table 1.
[0114] (1) Preparation of button cell: Lithium-ion battery cathode material, conductive agent Super P and binder PVDF were mixed in a mass ratio of 90:5:5. The slurry viscosity was controlled to 8000 mPa·s in a degassing machine. Then, the slurry was uniformly coated on aluminum foil using an automatic coating machine to form the original electrode sheet. The electrode sheet was dried in a vacuum oven at 130°C for 4 hours, and then placed in a forced-air oven at 80°C for 12 hours to obtain the test sheet. Several small electrode sheets were cut from different positions of the test sheet using a punch die with a diameter of 14 mm. Small electrode sheets with regular shape, smooth surface and edges were selected and weighed with a balance of 0.01%. The electrode sheets were placed in a vacuum drying oven and evacuated to 0.1 MPa to obtain the positive electrode sheet, which was then stored for later use. In an inert gas glove box with water and oxygen content of less than or equal to 0.0005%, coin cells were assembled according to the battery specifications of CR2023. The negative electrode was a lithium sheet, the separator was a polypropylene membrane, the high-voltage electrolyte solvent was a mixed solution of ethylene carbonate and diethyl carbonate with a volume ratio of 1:1, and the conductive salt was 1M lithium hexafluorophosphate. After assembly, the cells were encapsulated at 800 Pa for 5 seconds to obtain a coin cell.
[0115] (2) Initial performance test: At room temperature, it is charged to 4.60V at a constant current and constant voltage of 0.2C, with a cutoff current of 0.05C. After resting for 5 minutes, it is discharged to 3.0V at a constant current of 0.2C, where 1C = 160mAh / g.
[0116] (3) Rate performance test: At room temperature, it is charged to 4.60V at a constant current and constant voltage of 0.5C, with a cutoff current of 0.05C. After resting for 5 minutes, it is discharged to 3.0V at a constant current of 0.5C, where 1C = 160mAh / g.
[0117] Table 1
[0118]
[0119]
[0120] As shown in Table 1, compared with Comparative Examples 1 to 4, the lithium battery cathode material provided in this embodiment of the invention has a higher proportion of cross-sectionally penetrating broken particles, a higher charge / discharge capacity at 0.2C rate, and a higher discharge capacity retention rate at 1.0C / 0.2C, indicating good rate performance.
[0121] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention without departing from the principles and spirit of the present invention.
Claims
1. A lithium-ion battery cathode material, characterized in that, The lithium-ion battery cathode material comprises multiple particles, at least some of which have cracks extending from both ends to the particle surface, and the number of particles with such cracks accounts for more than 40% of the total number of particles in the lithium-ion battery cathode material; the general chemical formula of the lithium-ion battery cathode material is LiMa. 1-x Me x O2, wherein 0≤x≤0.05, Ma is selected from at least one of Co, Ni, and Mn, and Me is selected from at least one of Sc, Ti, V, Cr, Fe, Cu, and Zn.
2. The lithium-ion battery cathode material according to claim 1, characterized in that, The width of the crack is 20~300nm.
3. The lithium-ion battery cathode material according to claim 1, characterized in that, The length of the crack is 3~20μm.
4. The lithium-ion battery cathode material according to claim 1, characterized in that, The Ma contains Co, as well as Ni and / or Mn.
5. The lithium-ion battery cathode material according to claim 4, characterized in that, The molar ratio of Co to Ni and / or Mn is 1:(0.02~0.06).
6. The lithium-ion battery cathode material according to claim 1, characterized in that, The Me is selected from at least one of V, Ti, and Zn.
7. The lithium-ion battery cathode material according to claim 1, characterized in that, The particle size of the lithium battery cathode material is 3~20μm.
8. The lithium-ion battery cathode material according to claim 1, characterized in that, The compaction density of the lithium-ion battery cathode material is 4.15~4.25 g / cm³. 3 .
9. A method for preparing the lithium-ion battery cathode material according to any one of claims 1 to 8, characterized in that, The method includes the following steps: S1. The lithium battery cathode material precursor is mixed with a sodium source and then sintered to obtain an intermediate product; S2. The lithium source, reducing agent and intermediate product obtained in step S1 are mixed and subjected to a hydrothermal replacement reaction. The reducing agent is selected from at least one of oxalate, citrate, sulfite, nitrite and vitamin C. The molar ratio of lithium ions in the lithium source to sodium ions in the intermediate product is greater than 3:
1. The intermediate product is added 10~30°C before the reaction system is heated to the hydrothermal replacement reaction temperature. After the hydrothermal replacement reaction is completed, the solid is subjected to solid-liquid separation, water washing and drying. The resulting solid is the lithium battery cathode material. The general chemical formula of the lithium battery cathode material precursor is Ma. 1-x Me x O y Where 0≤x≤0.05, x and y satisfy the law of charge conservation, Ma is selected from at least one of Co, Ni, and Mn, and Me is selected from at least one of Sc, Ti, V, Cr, Fe, Cu, and Zn.
10. The method for preparing the lithium-ion battery cathode material according to claim 9, characterized in that, In step S1, Me is selected from at least one of V, Ti, and Zn.
11. The method for preparing the lithium battery cathode material according to claim 9, characterized in that, In step S1, the sodium source is selected from at least one of sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium nitrate, sodium sulfate, sodium acetate, and sodium oxalate.
12. The method for preparing the lithium battery cathode material according to claim 9, characterized in that, In step S1, the molar ratio of metal ions in the lithium battery cathode material precursor to sodium ions in the sodium source is 1:(0.75~1).
13. The method for preparing the lithium battery cathode material according to claim 9, characterized in that, In step S1, the sintering conditions include: a sintering temperature of 700~950℃ and a sintering time of 12~36h.
14. The method for preparing the lithium battery cathode material according to claim 9, characterized in that, In step S2, the lithium source is selected from at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium chloride, lithium bromide, and lithium iodide.
15. The method for preparing the lithium battery cathode material according to claim 9, characterized in that, In step S2, the molar ratio of the Ma source ion to the reducing agent in the intermediate product is 1:(0.05~0.25).
16. The method for preparing the lithium battery cathode material according to claim 9, characterized in that, In step S2, the conditions for the hydrothermal replacement reaction include: a reaction temperature of 100~180℃, a reaction time of 1~6h, a stirring frequency of 20~50Hz, and a reaction pressure of 0~2.0MPa.
17. The method for preparing the lithium-ion battery cathode material according to claim 9, characterized in that, In step S2, the solid content of the reaction system during the hydrothermal replacement reaction is 40~60wt%.
18. The method for preparing the lithium-ion battery cathode material according to claim 9, characterized in that, In step S2, the hydrothermal replacement reaction process includes: first mixing lithium source, reducing agent and water to obtain a premix, then heating the premix to 80~150℃ and adding intermediate product, and then continuing to heat the mixture to 100~180℃ to carry out the reaction.
19. The method for preparing the lithium-ion battery cathode material according to claim 18, characterized in that, In step S2, the heating rates of the premix and the mixture are each independently 1.0~1.5℃ / min.
20. The method for preparing the lithium battery cathode material according to claim 9, characterized in that, In step S2, the mass ratio of water to solid added during the washing process is (1~3):
1.
21. The method for preparing the lithium-ion battery cathode material according to claim 9, characterized in that, In step S2, the water washing is stopped when the concentration of metal ions in the water washing solution is below 200 ppm.
22. The application of the lithium-ion battery cathode material according to any one of claims 1 to 8 in lithium-ion batteries.
Citation Information
Patent Citations
Waste ternary positive electrode material single crystallization regeneration method
CN113437377A
Method for preparing ternary positive electrode material of lithium ion battery through mass transfer gradient driving
CN116443947A